KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI MODEL KOOPERATIF TIPE THINK TALK WRITE DI SMP PKPU ACEH BESAR - Uci Mahlisa; Nursiah (Jurnal Genta Mulia, 2024)
Good mathematical communication can improve learning outcomes. However, there are not many studies that reveal students' mathematical communication skills. This study aims to describe students' mathematical communication skills in solving problems during mathematics learning on social arithmetic material with a cooperative model of the think talk write type. This study was conducted in class VIIA of SMP PKPU Aceh Besar consisting of 23 students. The study used a qualitative approach with a descriptive research type. The subjects in this study were six students who had not met the KKM from the teacher, while the objects were the results of written tests and interviews with research subjects. To obtain research data, observations, interviews with research subjects, and tests were carried out. After all the data were collected, the qualitative data were analyzed descriptively, while the test result data were assessed based on the guidelines for assessing mathematical communication skills. Based on the data analysis, it can be concluded that students' mathematical communication skills through the application of the TTW cooperative learning model are influenced by students' mathematical abilities. Therefore, teachers can apply the TTW model in mathematics learning to improve students' mathematical communication skills.